2020
DOI: 10.1021/acs.orglett.0c02449
|View full text |Cite
|
Sign up to set email alerts
|

A Mild Method for Making MIDA Boronates

Abstract: We disclose that a predried form of methyliminodiacetic acid (MIDA), MIDA anhydride, acts as both a source of the MIDA ligand and an in situ desiccant to enable a mild and simple MIDA boronate synthesis procedure. This method expands the range of sensitive boronic acids that can be converted into their MIDA boronate counterparts. Further utilizing unique properties of MIDA boronates, we have developed a MIDA Boronate Maker Kit which enables the direct preparation and purification of MIDA boronates from boronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 104 publications
0
10
1
Order By: Relevance
“…Looking to the future of heterocycles in the SDM field, to the best of our knowledge, no reports exist demonstrating the use of cyclic boronic esters to produce SDMs. Cyclic boronic esters are ideal candidates for future investigations given their: long term stability, chemical orthogonality, 128 ease of synthesis, 129 commercial availability, and their facile transformation into amines, alcohols, thiols and halides. 130 Hence, in this section we will briefly outline their reactivity, and sketch potential future directions with illustrative examples focusing on pinacol (pin) and N-methyliminoacetic acid (MIDA) variants.…”
Section: Cyclic Boronic Estersmentioning
confidence: 99%
“…Looking to the future of heterocycles in the SDM field, to the best of our knowledge, no reports exist demonstrating the use of cyclic boronic esters to produce SDMs. Cyclic boronic esters are ideal candidates for future investigations given their: long term stability, chemical orthogonality, 128 ease of synthesis, 129 commercial availability, and their facile transformation into amines, alcohols, thiols and halides. 130 Hence, in this section we will briefly outline their reactivity, and sketch potential future directions with illustrative examples focusing on pinacol (pin) and N-methyliminoacetic acid (MIDA) variants.…”
Section: Cyclic Boronic Estersmentioning
confidence: 99%
“…Recently, we reported that the MIDA group could stabilize boron-containing polymers, and used them as a versatile approach for other organoboron compounds by post-polymerization transformations and for functionalized polymers by Suzuki–Miyaura coupling 48 . Interestingly, MIDA boronates showed significant differences in solubility compared with boronic acid and also an unusual binary affinity for silica gel, which enabled the rapid separation of MIDA boronate products 49 , 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of this contradictory nature, neither stability nor reactivity is perfect. Specifically, it is still difficult to fully avoid undesired degradation of B(pin) units during the transformations of other functional groups, and therefore B(pin) is not desirable as an M. Tougher boron units such as MIDA boronate 3 and B(dan) 4 are known to be tolerant to diverse reaction conditions because of their respective stabilization of the boron centre by intramolecular coordination and electron-donating amino groups. The reactivity of such protected boron units is, in turn, sacrificed and it is usually difficult to directly transform these boron functionalities without deprotection, with the exception of a few cases.…”
Section: Introductionmentioning
confidence: 99%